VD_FINDINFO HC / 2014 / 29 vom 30. September 2013 - VD Tribunal cantonal (2013)
DROIT D'EMPTION, PÉREMPTION, ENTREPRISE AGRICOLE DE PLAINE, SUCCESSION, UNITÉ DE MAIN-D'OEUVRE STANDARD, DROIT TRANSITOIRE, DROIT SUBJECTIF, DROIT FORMATEUR | 1 Tit. fin. CC, 681a al. 1 CC, 25 al. 1 let. b LDFR, 27 al. 1 LDFR, 42 al. 1 ch. 2 LDFR, 5 LDFR, 7 al. 1 LDFR, 1 LVLDFR, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 317 CPC (CH), 3 OTerm